2017
DOI: 10.1016/j.enpol.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Taking stock of the evolution of the biodiesel industry in Brazil: Business concentration and structural traits

Abstract: The Brazilian biodiesel industry has rapidly developed under the National Biodiesel Production and Use Programme (PNPB) launched in 2004, which is to be replaced by a new regulatory framework that is now under discussion. This paper aims to take stock of the evolution of the structure of the biodiesel industry in this country under the implementation of the PNPB-between 2005 and 2016-and to understand its current traits. The research combines a dynamic analysis of the industrial concentration indexes (closing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
2
7
0
1
Order By: Relevance
“…The search for alternative sources has continued to reduce competition in food crops to the extent that algae are used as a renewable and rich supply of biofuels known as third-generation biofuels [7]. Algae are not in a competitive environment with food or other crops and may be planted in shallow lagoons on marginal land or in enclosed wetlands [8].…”
Section: Introductionmentioning
confidence: 99%
“…The search for alternative sources has continued to reduce competition in food crops to the extent that algae are used as a renewable and rich supply of biofuels known as third-generation biofuels [7]. Algae are not in a competitive environment with food or other crops and may be planted in shallow lagoons on marginal land or in enclosed wetlands [8].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the HHI index remained the same in both periods, at 0.06, suggesting an unconcentrated industry. e top eight producer companies remained the same in both years, however, the order in the ranking changed (refer to Table 5) e number of economic groups decreased from 40 in 2013 to 35 by 2014, the drop of this number responds to acquisitions of some plants by other companies operating in the biodiesel market, due to business dynamism of the sector, as also observed by (Moreno-Pérez et al, 2017). It is worth noting that the increase in the volume of production can be attributed to the increase in mixture percentage from 5% to 7% in November 2014.…”
Section: Biodiesel Industry Concentration Ratio In 2012mentioning
confidence: 71%
“…e study of industrial organization, through the traditional structure-conduct-performance approach, has determined that concentration is influenced by the basic supply and demand conditions facing an industry. In the biodiesel industry, studies have shown that the industry is concentrated based on biodiesel production volume or sales volume (Tanaca & Souza, 2010;Leonardi, Scarton, Padula & Coronel, 2011;Cavalheiro, 2014;Moreno-Pérez, Marcossi & Ortiz-Miranda, 2017). Santos and Padula (2012) demonstrated that the biodiesel industry's dynamics shied from highly concentrated in 2005 to moderately concentrated in 2010, and even with the entrance of small biodiesel production plants, biodiesel production remained concentrated in large plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outras vantagens são a possibilidade de explorar a marca do SCS para promover sua imagem no mercado, a diferenciação/isenção nos tributos PIS/Pasep e Cofins, acesso às melhores condições de financiamento junto aos bancos que operam o programa e ter participação assegurada de 80% do biodiesel negociado nos leilões públicos da Agência Nacional de Petróleo, Gás Natural e Biocombustíveis -ANP (Abicht et al, 2014;dos Santos Alves et al, 2017;Moreno-Pérez et al, 2017).…”
Section: Biodiesel E Selo Combustível Socialunclassified